(China's Renewable Foreign Policy between Economic Interests and Western and African Restrictions - Sudan and South Sudan (2007-2017 - Ali, Muawiya Ali Musa (Journal of Economic, Administrative and Legal Sciences, 2018)
This paper presents an analysis of China's foreign policy towards the Africa in an effort to identify and explain any possible shift in its long-held previous strategy of non-interference in African affairs. China's economic relations in Africa have grown considerably over the past two decades, calling for the restructuring of these foreign policies. This paper concludes that three main factors - economic interests, Western pressure and African pressure - have forced China to adopt a more interventionist role in the internal affairs of African states. The paper aims to extrapolate, based on two case studies, the two countries of Sudan and South Sudan to know how these three factors played their role in changing the strategy of Chinese non-interference. It is also trying to identify what this shift in foreign policy may refer to globally.
Keywords: Chinese policy of non-interference; responsibility to protect; Western constraint; economic interests; African pressure; Sudan; South Sudan